2010
DOI: 10.1002/asia.201000614
|View full text |Cite
|
Sign up to set email alerts
|

Back‐Scattering Interferometry: A Versatile Platform for the Study of Free‐Solution versus Surface‐Immobilized Hybridization

Abstract: The first direct comparison of surface immobilization and free‐solution oligonucleotide hybridization using back‐scattering interferometry (BSI) showed that surface immobilization perturbs hybridization by as much as 50 %. BSI can distinguish between a perfect complement and a two‐base‐pair mismatch with an internal mismatch significantly destabilizing the duplex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Pesciotta et al studied the influence of mismatch position both in the bulk solution and on the surface. They also found that the dissociation constant K D for a DNA duplex is significantly larger on the surface than in the bulk solution . Bartlett et al used surface-enhanced Raman spectroscopy (SERS) to study the effect of electrochemical polarization upon thiol-linked dsDNA denaturation on gold electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…Pesciotta et al studied the influence of mismatch position both in the bulk solution and on the surface. They also found that the dissociation constant K D for a DNA duplex is significantly larger on the surface than in the bulk solution . Bartlett et al used surface-enhanced Raman spectroscopy (SERS) to study the effect of electrochemical polarization upon thiol-linked dsDNA denaturation on gold electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…25 This work highlights the unique capability of BSI to perform assays in both the hetero- and homogeneous format, allowing one to quantify how a surface attachment strategy or fluorophore will influence the performance of the methodology (Figure 7A). …”
Section: Backscattering Interferometrymentioning
confidence: 95%
“…24 Recently, we used BSI to begin to quantify some of the perturbations caused by adding a fluorophore to a DNA binding pair. 25 …”
Section: Applications Of Interferometrymentioning
confidence: 99%
“…26,28 The ability to measure these properties allows a wide array of interactions (antibodies to DNA to small molecules) to be quantified with a large range of affinities (μM to pM) regardless of the mass of the interacting species. 26,34,3739 Because RI changes may arise from molecular interactions unrelated to target binding, suitable blanks and controls must be prepared to ensure that the measured changes reflect an actual binding event. In addition, temperature control is employed to constrain background noise arising from thermal fluctuations.…”
mentioning
confidence: 99%